(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article examines the issue of the influence of the творчество of the prominent representative of Persian-Tajik literature, Nizami Ganjavi, on Uzbek classical literature. This issue is analyzed through the works of the fourteenth–fifteenth century Turkic poets Qutb Khwarazmi and Haydar Khwarazmi. It is emphasized that Turkic authors, continuing the tradition of Alisher Navoi, drew inspiration from the poems of the “Khamsa” and, through the method of free translation, produced distinctive didactic and romantic works. Furthermore, the similarities and differences between the works of Nizami and Turkic-speaking authors are elucidated through scholarly literary analyses and critical interpretations.